The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1973
DOI: 10.1037/h0035137
|View full text |Cite
|
Sign up to set email alerts
|

Personal characteristics of volunteer phone counselors.

Abstract: Comparisons between volunteer telephone counselors and nonvolunteer college students were made on several psychological tests: the Tennessee Self-Concept Scale, the Personal Orientation Inventory, and the Self-Disclosure Questionnaire. The results show no differences between the groups on their self-concept except in their moral-ethical perceptions of themselves. The groups did differ on the other measures. They showed a pattern of responding in the Personal Orientation Inventory suggesting that they were more… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0
3

Year Published

1977
1977
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 7 publications
1
19
0
3
Order By: Relevance
“…In fact, altruism has long been identified as a primary motivation by many authors (Esmond and Dunlop 2004;Howarth 1976;Tapp and Spanier 1973), and according to Monroe (1996) it can be considered as an incentive that will benefit others, even when this means a sacrifice for the welfare of the actor. Numerous authors identify altruistic and non-altruistic motivations as the concern of the individual with others and the self (Phillips 1982), career concerns (Frisch and Gerrard 1981), or leisure (Henderson 1981).…”
Section: Motivationsmentioning
confidence: 98%
“…In fact, altruism has long been identified as a primary motivation by many authors (Esmond and Dunlop 2004;Howarth 1976;Tapp and Spanier 1973), and according to Monroe (1996) it can be considered as an incentive that will benefit others, even when this means a sacrifice for the welfare of the actor. Numerous authors identify altruistic and non-altruistic motivations as the concern of the individual with others and the self (Phillips 1982), career concerns (Frisch and Gerrard 1981), or leisure (Henderson 1981).…”
Section: Motivationsmentioning
confidence: 98%
“…Theories on volunteer motives have been a central point in recent research, although additional research is required to identify primary reasons and motives for volunteering (Burns et al 2006;Briggs et al 2010). According to Esmond and Dunlop (2004) the first research in volunteer work appeared in the seventies, and altruism was one of the first motives identified (Tapp and Spanier 1973). In the eighties the volume of research on volunteer motivation grew (Esmond and Dunlop 2004) and produced the distinction between altruistic and egoistic motivations (Horton-Smith 1981;Phillips 1982).…”
Section: Motivationsmentioning
confidence: 99%
“…A number of studies have provided support for the use of volunteers in helplines (Knickerbocker, 1972;Paukert et al, 2004;Tapp & Spanier, 1973). King (1977) concluded that non-professionals were just as effective as professionals in providing support for callers.…”
Section: The Use Of Volunteers In Helplinesmentioning
confidence: 97%
“…However, despite the increasing use of volunteers in helplines, very little research is available on empathy levels and other personality characteristics in such individuals, or more generally on their motivation to volunteer (Wardell, Lishman, & Whalley, 2000). Tapp and Spanier (1973) compared volunteer telephone counsellors and a control group on several psychological tests. They suggested that volunteers displayed more self-actualising behaviour, had a greater capacity for open relationships with others, were more understanding, displayed more warmth and demonstrated higher levels of altruism.…”
Section: Characteristics Of Helpline Volunteersmentioning
confidence: 99%